THE ROLE OF INTERDEPENDENCIES BETWEEN CRITICAL INFRASTRUCTURES IN RURAL DEVELOPMENT - ASIMOPOLOS, Laurentiu A.; ASIMOPOLOS, Adrian-Aristide; ASIMOPOLOS, Natalia-Silvia (Annals of Spiru Haret University. Economic Series, 2018)
In the general context, the phenomenon of globalization causes an increase in risks to critical infrastructures. In order to order this set, the criteria of dependence and interdependence were imposed. Thus, was proposed a model with seven levels, the first being sector analysis and the second one the study of interdependencies. The first level is organized in critical sectors and dependencies between them. This division, which engendered the public-private partnership, is show on the EU and NATO documents. The second level of the interdependence study aims to determine the vital elements and essential components of a system. In this paper we show some considerations on the dimensionality of interdependencies between critical infrastructures, interdependence between critical infrastructures from the energy sector and Information and Communication Technology (ICT). After a breakdown of SCADA systems, we presented at the end of the paper few examples of cybernetic attack against energy infrastructures